KONDISI DAN KEANEKARAGAMAN JENIS KARANG BATU DI PULAU NUSALAUT, MALUKU TENGAH - Jemmy Souhoka (Universitas Gadjah Mada, 2009)
The purpose of this research was to identify the condition and diversity of hard corals in Nusalaut Island. The research was conducted in five locations of Nusalaut Island, Central Maluku District, namely Nalahia, Ameth, Titawai, Abubu and Akoon. Sampling by LIT (Line Intercept Transect) method was applied in December 2007. During the research, 123 species consisting 15 families were found. Hard coral was classified into midle to very good catagory, and the percentage of coverage was 26.96 to 80.08 %. Akoon island was good location and the diversity index was found 1.2 and evenness index was 0.69 respectively. In general, Nusalaut Island was dominated by Porites lutea with value 10.64% and Acropora formosa with value was 8.01% from all components.